المال وإستخداماته بوصفه أصلا في إصدار الصكوك في سوق الأوراق المالية - إدريس، عمر محمد
This thesis consists a comparative analytical study of concept of asset from two perspectives: from the Islamic juristic perspective on one hand, and the traditional western perspective on the other hand. The study aims at exploring a modern juristic view of the concept in order to allow a better understanding of the characteristics of an asset, and thus the definition of assets under which the issuance of sukuk is possible. The researcher used the inductive approach in order to present views of the scholars in the books of the Islamic heritage, as well as books of the contemporary jurisprudence, traditional finance, and other relevant research and studies that are conducted in the issue of asset. The researcher has also used the comparative and analytical approaches to combine the views of the various scholars and writers in order to arrive at an opinion which highlights the concept of asset more clearly. Through this study the issue of asset. The researcher found that the name “asset” could be attributed to anything (Tangible and non –tangible) that has a permissible benefit within the boundaries of the shari'ah common law, accepted according to the custom, and cam be disposed of within these boundaries. Thus he theory of asset possession is based on three elements: fulfillment of the financial identity in the item, fulfillment of the ownership of the plaintiff in the item, the plaintiffs' right and ability to use the item. The researcher concluded that sukuk may be issued based on anything that fulfills the identified characteristics of an asset as long as it does not lead to tricks or usury. The researcher has also put some shariah guidelines that govern the use of assets on relation to all stages of: sukuk issuance, sukuk trading, sukuk maturing.